RETRACTED: A nexus of social capital-based financing and farmers' scale operation, and its environmental impact - Li, Zenghui; Zhang, Zhixin; Elahi, Ehsan; Ding, Xin; Li, Jiaqi (Frontiers in Psychology, 2022)
The study constructs a theoretical model of social capital, farm household financing, and scale operation and their environmental effects, and conducts an empirical test based on data from China Family Panel Studies (CFPS) which is conducted in 2018. The results showed that farmers who spent more on human interaction have a higher probability of choosing scale operation by renting land, the mechanism of which is that the social capital accumulated by farmers based on human interaction facilitates their access to formal and informal financing, which in turn alleviates the financing constraint of scale operation. In addition, we found that the farmers with low education were more dependent on social capital to obtain informal financing to achieve scale operation. The environmental effects of scale operation found that the farmers significantly reduced the proportion of fertilizer and pesticide use, which could effectively mitigate possible pollution problems caused by excessive fertilizer and pesticide use. These findings confirm that social capital can alleviate the financing constraints of farmers to expand their operation scale through formal and informal financing, which in turn has a positive environmental effect.